The catalogue of bats in the collection of the department of evolutionary morphology of vertebrates of І. І. Scmalhauzen institute of zoology NAS of Ukraine - Kovalyova, I.M. (Збірник праць Зоологічного музею, 2015)
The collection of recent bats specimens kept in the Department of evolutionary morphology of I. I. Schmalhauzen Institute of Zoology of National Academy of Sciences of Ukraine was catalogued. The Catalogue presented here includes 11 families, 31 genera, and 56 species of bats (Mammalia, Chiroptera).